Economic behaviour and taxation (Edward Elgar E-Book Archive, 2016)
Recommended readings (Machine generated): Richard Blundell, Alan Duncan and Costas Meghir (1998), 'Estimating Labor Supply Responses using Tax Reforms', Econometrica, 66 (4), July, 827-61 -- Sören Blomquist and Whitney Newey (2002), 'Nonparametric Estimation with Nonlinear Budget Sets', Econometrica, 70 (6), November, 2455-80 -- Anil Kumar (2008), 'Labor Supply, Deadweight Loss and Tax Reform -- Austan Goolsbee (2000), 'What Happens When You Tax the Rich? Evidence from Executive Compensation', Journal of Political Economy, 108 (2), April, 352-78 -- Emmanuel Saez (2010), 'Do Taxpayers Bunch at Kink Points?', American Economic Journal: Economic Policy, 2 (3), August, 180-212 -- Wojciech Kopczuk (2005), 'Tax Bases, Tax Rates and the Elasticity of Reported Income', Journal of Public Economics, 89 (11-12), December, 2093-119 --